Building Sustainability Assessment throughout Multicriteria Decision Making. (30th September 2013) - VillarinhoRosa, Lúcio; Haddad, Assed Naked
Abstract : Opinion and choice strongly influence sustainability concepts. The building construction industry, in particular property developers, has been charged with promoting excess environmental impacts ranging from overuse of resources to pollution generation. This paper presents an application of sustainability concepts to building projects, as well as to the development of practices, methodology, and tools for evaluating existing buildings. This study will detail how current systems to evaluate building performance operate and how to improve them. This approach utilizes the analytic hierarchy process (AHP). AHP is a multicriteria method that evaluates the relative importance of criteria, subcriteria, and families of indicators, used in the proposed system of technical characteristics applied to the local culture. At the same time, AHP makes visible the critical factors involved in evaluation of sustainability of these buildings. A result of the application of this type of modeling is a system for sustainability assessment and evaluation of environmental aspects and socioeconomic perspectives of existing buildings in the state of Rio de Janeiro, Brazil.